2007
DOI: 10.1177/0256090920070302
|View full text |Cite
|
Sign up to set email alerts
|

Pay Satisfaction of Software Professionals in India

Abstract: This study explores pay satisfaction-related issues of software professionals in India, specifically assessing the impact of different dimensions of pay satisfaction on intent to leave. Since satisfaction with pay is an emotional/affective reaction and is likely to be influenced by personal and environmental factors, the study explores some social psychological processes like leader-member exchange, justice, and voice that are likely to impact pay satisfaction of these professionals. Using a sample of 306 soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…In global IT careers, factors such as better job scopes outside the present organization, perceived vocational alternatives, job satisfaction, workplace stress, and burnout were some of the reasons for quitting intention (Joseph, Ng, Koh, & Ang, 2007). Among Indian IT employees, such intention was related to lucrative job offers that matched salary demands, interest, skills and competencies (Ghapanchi & Aurum, 2011), domestic issues (Aboobaker, Edward, & Pramatha, 2017), sociocultural and demographic norms (Lacity et al, 2008), pay dissatisfaction (Bhal & Gulati, 2007), innovative career passions (Victor, 2011) and so on. Findings across literature implied IT professionals’ turnover cogitation as a key concern of human resource management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In global IT careers, factors such as better job scopes outside the present organization, perceived vocational alternatives, job satisfaction, workplace stress, and burnout were some of the reasons for quitting intention (Joseph, Ng, Koh, & Ang, 2007). Among Indian IT employees, such intention was related to lucrative job offers that matched salary demands, interest, skills and competencies (Ghapanchi & Aurum, 2011), domestic issues (Aboobaker, Edward, & Pramatha, 2017), sociocultural and demographic norms (Lacity et al, 2008), pay dissatisfaction (Bhal & Gulati, 2007), innovative career passions (Victor, 2011) and so on. Findings across literature implied IT professionals’ turnover cogitation as a key concern of human resource management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, literature considers career satisfaction as an important vocational attitude in the contemporary world of work, but it remains an unexplored concept in Indian IT occupational domain. Perhaps, extant studies convey that satisfaction in Indian IT careers is mainly linked to the notion of job satisfaction, pay-satisfaction, and work–life balance (Bhal & Gulati, 2007; Lacity, Iyer, & Rudramuniyaiah, 2008; Singh, 2010). Furthermore, researchers annotate employees’ turnover intent, which is a key focus of the Indian IT industry and has to be understood from different perspectives (Lacity et al, 2008).…”
mentioning
confidence: 99%
“…As an example, the study by Bhal and Gulati (2007) revealed that process-related dimensions, for example, performance orientation of rewards, impact job satisfaction and thus employee willingness to stay with their current employer. A reason for this is that performance-related rewards are perceived as fairer than traditional…”
Section: Personnel Retention Practices and Effi Ciencymentioning
confidence: 99%
“…In addition, we see that the manager-subordinate relationship may weaken the effect of contextual communication orientation on promotive voice. Past research indicates that high LMX enhances voice behavior (Bhal & Gulati, 2006, 2007Botero & Van Dyne, 2009;Burris, Detert, & Chiaburu, 2008;Hsiung, 2012;Van Dyne, Kamdar, & Joireman, 2008). The current study indicates that LMX may have different effects on high-versus low-context communicators, such that high-context communicators receive greater benefit in terms of self-expression than others from a strong relationship with the manager.…”
Section: Discussionmentioning
confidence: 99%